THE EFFECT OF CO2 ON THE GEOMECHANICAL AND PERMEABILITY BEHAVIOUR OF BROWN COAL: IMPLICATIONS FOR COAL SEAM CO2 SEQUESTRATION - Viete D.R.; Ranjith P.G. (My University, 2006)
Theory from fracture mechanics and thermodynamics coupled with the results of experimental studies provides evidence to suggest that the adsorption of carbon dioxide on coal causes a decrease in the coal strength. Coal weakening by the introduction of CO2 to a coal seam may induce fracturing, causing a permeability increase under in situ conditions. Such effects present significant implications for proposals regarding the storage of CO2 in coal seams. A uniaxial and triaxial laboratory study was carried out to explore the effects of the adsorption of CO2 on the compressive strength and permeability of southeast Australian brown coal. Comparison of the stress-strain response of air-saturated and CO2-saturated specimens revealed a compressive strength decrease in the order of 13% and an elastic modulus decrease of about 26% for the uniaxial testing, but no significant strength or elastic modulus decrease for the triaxial testing. The absence of an adsorptive effect on the mechanical behaviour of the triaxial specimens may have been due to an insufficient saturation period under simulated ground conditions, or due to mechanical variability in the brown coal test specimens, however, further testing is required to reveal the reason for the apparent negligible strength reduction with CO2 adsorption at the higher confinement. Carbon dioxide outflow measurements during the stress-strain process demonstrated an initial permeability decrease with pore closure, followed by a significant increase in specimen permeability with fracturing. Issues that require consideration in the application of these results to coal seam CO2 sequestration include: whether the expected regional and localised in situ stresses are sufficient to initiate fracturing with adsorptive weakening; how coal properties (e.g. rank, moisture content) are likely to affect the geomechanical influence of CO2 adsorption, and the expected magnitude of the proposed fracture related permeability increase. © 2005 Elsevier B.V. All rights reserved.
Keywords: ADSORPTIVE WEAKENING; CO; COAL; GEOMECHANICS; PERMEABILITY